The Population Ecology of Organizations (translated by Gregory Yudin) - Michael T. Hannan; John Freeman (Journal of Economic Sociology, 2013)
A population ecology perspective on organization-environment relations is proposed as an alternative to thedominant adaptation perspective. The strength of inertial pressures on organizational structure suggests theapplication of models that depend on competition and selection in populations of organizations. Several suchmodels, as well as issues arising in attempts to apply them to the organization-environment problem, arediscussed.